The Effect of Softening of Gutta-Percha Using Cajuput Oil in Root Canal Filling with Epoxy Resin and Glass Ionomer Cements Sealers - Erma Sofiani; Astri Bilqis Azizah (Denta Journal Kedokteran Gigi, 2021)
Background: The failure of root canal treatment is non-hermetic obturation. It could be prevented with the use of sealer material. The sealer with an excellent bond to the dentin is epoxy  resin and glass ionomer cement sealer. Eucalyptus oil is a natural substance that could dissolve gutta-percha because it has an antimicrobial effect and is biocompatible. Objective: To determine the effect of softening with Cajuput Oil on root canal filling with epoxy resin and glass ionomer cement sealers. Methods: The design of this study was pure laboratory experimental, 24 samples of single root canal  block, each block was prepared with step back technique and obturation with lateral condensation. The samples were treated differently by the type of sealer used and incubation time. Group of treatment will be dripped with 0.1 ml of cajuput oil for 5 minutes. Compressive loading was performed apico-coronally by Universal testing machine using cylindrical stainless-steel plunger speed of 2 mm/min until softening occurred. The data were processed using a one-way ANOVA and Post-Hoc Tukey test with a significance level of 95% (p <0,05). Results: There was a significant effect of epoxy bisphenol resin sealer and Glass Ionomer Cement sealer in softening gutta-percha using cajuput oil. The epoxy resin sealer, which was incubated for 22 days after contact with cajuput oil for 5 minutes, had a higher softening value than others. Conclusion: Sealer epoxy bisphenol resin is easier  to remove than the Glass Ionomer Cement sealer with cajuput oil solvent at 22 days after incubation.